2007
DOI: 10.1590/s0100-06832007000600008
|View full text |Cite
|
Sign up to set email alerts
|

Interestratificado caulinita-esmectita em um argissolo desenvolvido a partir de rocha sedimentar do Sul do Brasil

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
1
10
0
3
Order By: Relevance
“…The experiment was set up in 1991 in a Typic Hapludalf (Argissolo Vermelho distrófico típico) (Embrapa, 2006), with a sandstone substrate. At the 0-20 cm layer, the soil presented 180 g kg -1 of clay, composed of kaolinite, interstratified illite-smectite (Moterle, 2008) and kaolinite-smectitee (Bortoluzzi et al, 2007) In implantation of the experiment, 3.0 Mg ha -1 of dolomitic lime was applied and incorporated to elevate the pH in the water of the soil to 6.0. Treatments were arranged in subdivided plots with a randomized block experimental design with four replications, applied on the summer crops.…”
Section: Methodsmentioning
confidence: 99%
“…The experiment was set up in 1991 in a Typic Hapludalf (Argissolo Vermelho distrófico típico) (Embrapa, 2006), with a sandstone substrate. At the 0-20 cm layer, the soil presented 180 g kg -1 of clay, composed of kaolinite, interstratified illite-smectite (Moterle, 2008) and kaolinite-smectitee (Bortoluzzi et al, 2007) In implantation of the experiment, 3.0 Mg ha -1 of dolomitic lime was applied and incorporated to elevate the pH in the water of the soil to 6.0. Treatments were arranged in subdivided plots with a randomized block experimental design with four replications, applied on the summer crops.…”
Section: Methodsmentioning
confidence: 99%
“…The observed interstratifications may be related to better drainage under current hydropedological conditions, where part of the K present between the layers of the illite is lost, becoming smectite (Bortoluzzi et al, 2005). Afterwards, as the process advances, part of the Si present in the siloxane layers is removed from the structure (desilication), resulting in the formation of the kaolinite phase of the interlayer (Bortoluzzi et al, 2007). Despite the significant presence of 2:1 clay minerals in the P5 profile, the low values of clay fraction activity are probably due to the higher proportion of coarse clay and its predominantly kaolinitic constitution (data not shown).…”
Section: Soil Properties and Pedogenetic Processesmentioning
confidence: 98%
“…In addition, the peak decompositions centered at d = 0.72 nm showed that two kaolinite populations were present, one well crystallized with a high coherent scattering domain size (CSDS) at d = 0.72-0.73 nm, and one with a low CSDS (poorly crystallized) at d = 0.75 nm, which contributed to 11.8-21.0 % of the diffracted intensity (Figure 3). Interstratified kaolinite-smectite was not present because there was no peak at d = 0.72 nm displacement after EG solvation (Bortoluzzi et al, 2007).…”
Section: Mineralogy Of the Different Soil Fractionsmentioning
confidence: 99%